Usefulness of the anterior lumbar interbody fusion (ALIF) technique in failed back surgery syndrome - Yataco Wilcas, Christian Alexander (2024)
Failed back surgery syndrome is a postsurgical phenomenon that involves persistent low back pain following one or more spinal surgeries. The multidisciplinary approach to its management includes both conservative and surgical treatments. Anterior lumbar interbody fusion (ALIF) has stood out as a surgical option for refractory pain. We present five cases of patients with failed back surgery syndrome treated with ALIF. These patients demonstrated reduced pain scale scores and significant improvement in functional capacity after the application of the abovementioned technique, suggesting its effectiveness in this group of patients who are refractory to conservative treatments. It should be noted that previous studies supporting the usefulness of ALIF mention the importance of careful patient screening, considering both preoperative factors (pain pathophysiology and accurate assessment of the underlying cause) and postoperative factors (pain recurrence and biomechanical changes), to ensure the success of the technique. Therefore, while ALIF appears to be a promising surgical option for these patients—whose condition is challenging—the need for further studies with larger samples is highlighted to provide stronger scientific evidence supporting its efficacy for this condition.